2019
DOI: 10.1016/j.isci.2019.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer Aβ Assemblies Accumulate in Excitatory Neurons upon Proteasome Inhibition and Kill Nearby NAKα3 Neurons by Secretion

Abstract: Summary We identified ∼30-mer amyloid-β protein (Aβ) assemblies, termed amylospheroids, from brains of patients with Alzheimer disease (AD) as toxic entities responsible for neurodegeneration and showed that Na + ,K + -ATPase α3 (NAKα3) is the sole target of amylospheroid-mediated neurodegeneration. However, it remains unclear where in neurons amylospheroids form and how they reach their targets to induce neurodegeneration. Here, we present an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 83 publications
1
22
0
Order By: Relevance
“…Wang et al reported that HAPLN2 involved in the pathogenesis of schizophrenia by regulating the neuron migration and velocity of nerve conduction [67]. Similarly, Komura et al found that amyl spheroids were accumulated mainly in the trans-golgi network of excitatory neuronal cells, causing the degeneration of adjacent NAKα3-expressing neurons in Alzheimer's disease [68]. In the present study, we found that the number of microglia and astrocytes were elevated in BTI model with miR-7 deficiency.…”
Section: Discussionsupporting
confidence: 64%
“…Wang et al reported that HAPLN2 involved in the pathogenesis of schizophrenia by regulating the neuron migration and velocity of nerve conduction [67]. Similarly, Komura et al found that amyl spheroids were accumulated mainly in the trans-golgi network of excitatory neuronal cells, causing the degeneration of adjacent NAKα3-expressing neurons in Alzheimer's disease [68]. In the present study, we found that the number of microglia and astrocytes were elevated in BTI model with miR-7 deficiency.…”
Section: Discussionsupporting
confidence: 64%
“…After binding to the fourth extracellular loop (Ex4) of Na + /K + -ATPase α3 subunit (NAKα3) in neurons, brain-derived ASPD cause the impairment of NAKα3-specific activity and the activation of N-type voltage-gated calcium channels, both of which can increase cytoplasmic Ca 2+ levels and induce mitochondrial calcium dyshomeostasis, leading to mature neurons death and cognitive impairment eventually [ 20 , 114 ]. Further research on the distribution and spread of ASPD among different neurons identified that ASPD mainly accumulated in the trans-Golgi network of excitatory neurons and after secreted by these neurons, ASPD invaded and caused the death of surrounding NAKα3-positive neurons [ 136 ]. In general, ASPD are Aβos with unique conformation and robust neurotoxicity.…”
Section: The Polymorphism Of Aβosmentioning
confidence: 99%
“…However, it is still unclear how the amylospheroids are secreted from the neurons where they are formed. Our preliminary results suggest that amylospheroid may be passed trans-synaptically via a so far unknown mechanism (Komura et al, 2019). If this is truly the case, it would be difficult to access the very crowded intersynaptic space with a full-size antibody to achieve an inhibitory effect.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 86%
“…In this review, I have discussed three different treatment strategies for AD, focusing on work in my laboratory as an example. Importantly, we found that amylospheroids are formed only in excitatory neurons and exert their toxicity after being secreted extracellularly (Komura et al, 2019). However, it is still unclear how the amylospheroids are secreted from the neurons where they are formed.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 87%
See 1 more Smart Citation